Factors Associated to Canalith Repositioning Procedure Failure in Benign Paroxysmal Positional Vertigo Patients (2016)
ABSTRACT: Purpose: To explore factors associated to treatment failure by canalith repositioning procedures (CRP) in benign paroxysmal positional vertigo (BPPV) patients and to describe its clinical and socio-demographical characteristics. Methods: An observational cohort study was conducted by a review of medical records of vertigo cases at Clinica ORLANT in Medellin, Colombia. Results: This study included eighty-six patients with BPPV diagnosis who had undergone CRP and clinical followup for one to four weeks to evaluate treatment failure. Here, 91.9% were women with median age of 63.06 years (28 to 86), 44.2% had left posterior canal BPPV, 46.5% had right posterior canal BPPV, 1.2% had bilateral posterior canal BPPV, 1.2% had left lateral canal BPPV, 4.7% had right lateral canal BPPV, and 2.3% had bilateral lateral canal BPPV. Also, 56.97% of patients presented treatment failure, where an association was identified between vestibular neuritis (OR: 1.787 CI: 1.478–2.161) and migraine (OR: 1.822 CI: 1.497–2.217). No statistically significant associations were found between comorbidities such as dyslipidemia, high blood pressure, diabetes mellitus, hypothyroidism, and traumatic brain injury. Prior consumption of Ginkgo Biloba found in 22.1% of patients was associated with a lower risk of presenting treatment failure (OR: 0.347 CI: 0.121–0.998). In addition, 17.4% of patients were referred to vestibular rehabilitation therapy. Conclusion: The risk factors for treatment failure by CRP in BPPV are a controversial topic and require further research. Due to the sample size, strong associations cannot be determined; however, the possible protective role of Ginkgo Biloba remains an issue to be considered.